Ekplorasi Gerak dan Ekspresi Tari Bedhaya Kalang di Sanggar Nyi Pandansari Kabupaten Kendal - Septina Dwi Widyaningrum; Eny Kusumastuti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to dissect in more depth the process of movement exploration and the embodiment of expression in the Bedhaya Kalang dance, an innovative dance work at the Nyi Pandansari Studio, Kendal Regency. This dance is an artistic representation of the Mendhak Kalang Obong ritual of the Kalang tribe. This study uses a qualitative method with an ethnographic approach. Data were collected through participatory observation, in-depth interviews with the choreographer, and performance documentation. The results show that the movement exploration in the Bedhaya Kalang dance is the result of a hybridization between the basic movements of Surakarta-style classical female dance with elements of masculinity derived from pencak silat movements and stylized buffalo movements. The exploration process is carried out through intensive body conditioning stages and repetitive exercises to achieve large, strong, and fast yet graceful movement qualities. Expressively, this dance successfully displays the duality of character, namely the gentleness of a woman and the steadfastness of the Kalang tribe. The whip property becomes the main instrument in exploring the dexterity of the dancers' movements and expressions. This study concludes that the exploration of movement in Bedhaya Kalang is not merely an aesthetic innovation, but rather an attempt to articulate the cultural identity of the Kalang tribe which is manifested through the dancer's bodily expression.